PENGARUH BUDAYA ORGANISASI, PENGENDALIAN INTERNAL DAN KEJELASAN SASARAN ANGGARAN PADA AKUNTABILITAS KINERJA SKPD KABUPATEN GIANYAR DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERASI - Dewi, Kadek Fitria; Widana Putra, A.A.G.P; Putra Astika, Ida Bagus (Buletin Studi Ekonomi, 2017)
This study was conducted to discuss the performance accountability of SKPD Gianyar regency. The purpose of this study was to determine the influence of organizational culture, internal control and budget goal clarity on accountability of SKPD performance and to determine the role of organizational commitment in moderation. The sampling method used is saturated with a sample of respondents was 108 respondents. Data used in the form of primary data using questionnaires. The analysis technique used is regression analysis moderation (Moderated Regression Analysis). The results showed that organizational commitment and strengthen the influence of organizational culture on a budget goal clarity Gianyar regency SKPD performance accountability. Commitment organizations are not able to moderate the influence of internal controls Accountability SKPD performance.